A quilting subcutaneous suture pattern to reduce seroma formation and pain 24 hours after midline celiotomy in dogs: A randomized controlled trial. Issue 2 (3rd December 2017) - Travis, Blake M.; Hayes, Galina M.; Vissio, K.; Harvey, H. J.; Flanders, James A.; Sumner, Julia P.
Abstract: Objective: To determine the influence of a quilting suture pattern tacking the subcutaneous tissues to the deep fascia on complications after midline celiotomy in dogs. Study design: Single‐center, randomized, blinded, controlled trial conducted in a veterinary teaching hospital. Animals: Four hundred thirty‐two dogs undergoing midline celiotomy for ovariohysterectomy (n = 249) or other abdominal procedures (n = 183). Methods: Dogs were randomly assigned to (1) a quilting group, subcutaneous tissue with apposition plus tacking to the rectus fascia or (2) a nonquilting group, with apposition of subcutaneous tissue without tacking. Randomization was stratified on hospital admitting service. Primary outcome was the incidence of incisional seroma. Secondary outcomes included postoperative pain the day after surgery and surgical site infection (SSI). Outcomes were assessed during the first 30 postoperative days. Results: No differences were detected between the quilting group (n = 183) and the nonquilting group (n = 175) in terms of illness severity, surgical procedure performed, surgeon's experience, duration of surgery, intraoperative complications, or methods of surgical closure other than the intervention under study. In an intent‐to‐treat analysis, the incidence of incisional seroma was lower in the quilting group (odds ratio = 0.30, 95% CI = 0.13‐0.67, P  = .004). Pain assessed 24 hours postoperatively was lower in the quilting group ( P  = .03). The incidence of SSI did not differ between groups. Conclusion: Tacking the subcutaneous tissues to the deep fascia is indicated to reduce seroma during celiotomy closure.